Rotational spectroscopy of a triatomic molecular anion - Lakhmanskaya, Olga; Simpson, Malcolm; Murauer, Simon; Nötzold, Markus; Endres, Eric; Kokoouline, Viatcheslav; Wester, Roland (Physical review letters, 2018)
Rotational transitions of the nonlinear triatomic molecular anion NH2− have been observed by terahertz spectroscopy in a cryogenic radio frequency ion trap. Absorption of terahertz photons has been probed by rotational state-dependent photodetachment of the trapped negative ions near the detachment threshold. Using this two-photon scheme, the two lowest rotational transitions for the asymmetric top rotor NH2− have been found. For the para nuclear spin configuration, the 10←00 transition frequency was determined to be 933 954(2) MHz, and for the ortho configuration the 1+1←1−1 transition frequency was determined to be 447 375(3) MHz. This result appears to preclude the recent tentative assignment of an interstellar absorption feature to NH2−.